Terorisme di Era Digital: Kajian Teoritis Perkembangan Upaya Penanggulangan Hukum Sejak Era Orde Baru Hingga Memasuki Era Digital - Safri HM; ST Laksanto Utomo; Lukman Hakim (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Terrorism has been a serious threat to national and global security for decades. In Indonesia, the phenomenon of terrorism exhibits a dynamic pattern of development, both in terms of ideology, modus operandi, and attack targets. This evolution is inseparable from ongoing social, political, and technological changes. In recent years, advances in information and communication technology have created a new chapter in the threat of terrorism. The internet and social media are widely used by terrorist groups to spread radical propaganda, recruit new members, communicate, and raise funds online. This development presents a significant challenge for law enforcement. Terrorist modus operandi has become more decentralized, no longer dependent on conventional structured networks. The research method used in this study is a normative juridical research method. The materials reviewed include primary, secondary, and tertiary legal materials. The results show that the development of counterterrorism efforts in Indonesia shows a shift from a militaristic approach to a more comprehensive criminal approach. These developments involved strengthening the rule of law (from Law No. 15/2003 to Law No. 5/2018), the establishment of specialized institutions (Densus 88 and BNPT), and the adoption of more progressive legal theories. While these efforts have yielded significant results, challenges persist, requiring ongoing strategic adaptation